An Analysis of Power Dynamics in Leigh Bardugo's Six of Crows (2015) - Nadia Ramadhiani Ranaputri; Safrina Noorman (Universitas Pendidikan Indonesia (UPI), 2020)
This research aims to analyze the portrayal of power dynamics in Leigh Bardugo’s young adult novel Six of Crows. The study uses qualitative descriptive method to analyze how power dynamics is portrayed in the novel. Data was collected through textual evidence that showcases the exercise of power and analyzed based on Foucault’s (1982) theory of power. The study finds that power dynamics is portrayed through a series of conflicts between the six main characters. These conflicts are mostly verbal. Power is exercised in the form of arguments and bickers, in which of the six characters attempt to constantly gain authority and power over one another. Among the six characters, conflicts and exercise of power can be found in four notable character pairings. The power that is exercised is seen through exploitation of one’s desires, expressions of judgment and hatred, as well as physical conflict in some cases.Keywords: Characters, Foucault, Power, Power dynamics, Six of crows, Young adult.